The Influence of Human Capital Management on E-Government Service Reliability in Indonesian Public Institutions - Harjono K., Maykada; Wildan, Moh. (Jurnal Manajemen Indonesia, 2025)
This study examines the influence of institutional trustworthiness and perceived information security on the reliability of e-government services, with strategic human capital alignment as a mediating variable. A quantitative survey was conducted among 150 government administrators managing digital services under the official ‘go.id’ domain. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results show that institutional trustworthiness significantly affects both human capital alignment and perceived service reliability, while perceived information security influences only internal alignment. However, the mediating effect of human capital alignment is not supported. These findings suggest that public trust in digital services is more influenced by institutional legitimacy than technical security or internal initiatives. The study highlights the need to align human capital development—such as training, procedural readiness, and national programs like the Digital Talent Scholarship—with strategic performance goals to enhance service credibility. Practical and theoretical implications are discussed for public sector digital governance.